The Fading Revolutionary Capacity of the Zombi? The Transformation of Zombis’ Symbolism in Haitian Literature as Exemplified by the Novels of Dany Laferrière and Yanick Lahens - Poręba, Izabela (2023)
Zombis, unlike the zombies prevalent in American pop culture, function in Haitian culture as complex symbols with historically variable meanings – initially depicting the process of enslavement during the transatlantic slave trade, they increasingly became symbols of Haitian revolutions and resistance. This dialectical doubling of the meaning of zombis can still be found in Dany Laferrière’s novel Pays sans chapeau, published in 1996. The article reconstructs the origin of zombis, presents a discussion on the meaning of this figure, including dialectical views, and discusses their fictional depictions. The aim of the article is to investigate whether zombis still have a twofold symbolism in narrative, as symbols of both enslavement and revolutionary resistance. By considering the vestigial reminiscences of zombis in Yanick Lahens’ novel Douces déroutes, attention is drawn to the processes of gradual loss of zombis’ ambivalence and their importance as means of creating Haitian identity and everyday experience. According to the study’s conclusions, their absence (or their residual forms) in the novel of the second decade of the 21st century is as significant and interesting as their vitality and omnipresence in the works of writers of previous generations.
Keywords: Laferrière, Dany; Lahens, Yanick